Risk factors for mortality in hemodialysis patients: two-year follow-up study - do Sameiro-Faria, Maria (2013)
End-stage renal disease (ESRD) patients under hemodialysis (HD) have high mortality rate. Inflammation, dyslipidemia, disturbances in erythropoiesis, iron metabolism, endothelial function, and nutritional status have been reported in these patients. Our aim was to identify any significant association of death with these disturbances, by performing a two-year follow-up study. Methods and Results. A large set of data was obtained from 189 HD patients (55.0% male; 66.4 ± 13.9 years old), including hematological data, lipid profile, iron metabolism, nutritional, inflammatory, and endothelial (dys)function markers, and dialysis adequacy. Results. 35 patients (18.5%) died along the follow-up period. Our data showed that the type of vascular access, C-reactive protein (CRP), and triglycerides (TG) are significant predictors of death. The risk of death was higher in patients using central venous catheter (CVC) (Hazard ratio [HR] =3.03, 95% CI = 1.49–6.13), with higher CRP levels (fourth quartile), compared with those with lower levels (first quartile) (HR = 17.3, 95% CI = 2.40–124.9). Patients with higher TG levels (fourth quartile) presented a lower risk of death, compared with those with the lower TG levels (first quartile) (HR = 0.18, 95% CI = 0.05–0.58). Conclusions. The use of CVC, high CRP, and low TG values seem to be independent risk factors for mortality in HD patients.